The Theology of Beauty in Kudus Minaret’s Architecture: A Study of Javaness-Hindu-Islamic Acculturation - Wijaya Wijaya (Yayasan Adra Karima Hubbi, 2025)
The Kudus Tower adopts a form resembling a Hindu-Buddhist temple, raising important questions about the theological meaning of beauty and symbolism in Islamic architecture. This study aims to examine how the theology of beauty is articulated through the architectural form of the Kudus Tower and how Javanese, Hindu, and Islamic elements are harmoniously integrated within it. Using a qualitative research design, the study utilizes historical-architectural analysis, visual interpretation, and textual examination of classical Islamic and Javanese sources, complemented by secondary literature on acculturation and aesthetics. The findings indicate that the Kudus Tower embodies a contextual Islamic aesthetic that emphasizes harmony, tolerance, and local cultural continuity, rather than architectural fragmentation. Its form reflects a theological understanding of beauty as a means of da'wah, enabling Islam to be accepted without negating existing cultural identities. The study concludes that the Kudus Tower is not simply an architectural anomaly, but a profound expression of Islamic theology of beauty that accommodates local wisdom and encourages peaceful religious acculturation. This research contributes to broader discussions on Islamic aesthetics, cultural hybridity, and contextual religious expression in Southeast Asia.